BIO-INSECTICIDAL ACTIVITY OF CORIANDER (CORIANDRUM SATIVUM) LEAVES POWDER AGAINST COWPEA BRUCHID (CALLOSOBRUCHUS MACULATUS (FABRICUS) COLEOPTERA: CHRYSOMELIDAE) ON STORED CHICKPEA (CICER ARIETINUM (L.) (WALPER) - Bukar, Ahmadu; Dawud, Amina M.; Kumshe, Isa B.; Mohammed, Zubairu (FUDMA JOURNAL OF SCIENCES, 2025)
Laboratory experiment was carried out to assess the insecticidal activity of coriander leaves powder against Callosobruchus maculatus (F.). The leaves powder were applied at 1.0, 1.5, 2.0, 2.5 and 3.0 g/kg of chickpea and the 0.0g/kg untreated seeds served as control. The experiment was laid out in a Complete Randomized Design with six treatments replicated three times. Data collected were adult mortality, oviposition rate, F1 progeny emergence, seeds damage, weight loss, weevil perforated index and seeds germination were carried out. Significant difference (P<0.05), were recorded between the chickpea, dose and exposure period after treatment. The results obtained showed that the plant powder was very effective in protecting stored chickpea against C. maculatus at the highest dosage (3.0 g/kg) 120 hrs after treatment where complete 100% adult mortality were observed. There was no F1 progeny emergence of C. maculatus in chickpea treated at the dosage of 3.0 g/kg, while, at the same dosage, almost completely inhibited the F1 progeny emergence. Also, the different dosage levels significantly protected the seeds against seed damage and weight loss caused by C. maculatus compared with the untreated control after 60 days of storage. The viability of seeds was not affected by the leaves powder. Therefore, the leaves powder could be a good candidate in insect pest management, especially against C. maculatus in stored chickpea seeds.